Canonical Decomposition of Outerplanar Maps and Application to Enumeration, Coding and Generation - Bonichon, Nicolas; Gavoille, Cyril; Hanusse, Nicolas (Journal of Graph Algorithms and Applications, 2005)
In this article we define a canonical decomposition of rooted outerplanar maps into a spanning tree and a list of edges. This decomposition, constructible in linear time in the Word-RAM model, implies the existence of bijection between rooted outerplanar maps with n nodes and bicolored rooted ordered trees with n nodes where all the nodes of the last branch are colored white. As a consequence, for rooted outerplanar maps of n nodes, we derive: <!—-> an enumeration formula, and an asymptotic of 23n −Θ(logn); <!—-> an optimal data structure of asymptotically 3n bits, built in O(n) time, supporting adjacency and degree queries in worst-case <!—-> constant time and neighbors query of a degree-d node in worst-case O(d) time. <!—-> an O(n) expected time uniform random generating algorithm. <!—-> <!—->